Eco-Theological Insights on The Sasi Tradition: Analyzing Environmental Ethics and Sanctions Through Fiqh al-Bi'ah and Islamic Criminal Law - Haq, Islamul; L, Sudirman; Amiruddin, Muhammad Majdy (Institut Agama Islam Negeri Curup, 2025)
Environmental preservation is a crucial issue that continues to receive attention, especially amid growing concerns about environmental degradation caused by human activities. This study aims to examine the implementation of the sasi mechanism by the people of Negeri Iha, Seram Island, and Ambon and to analyze the cultural significance of the sasi system regarding the concepts of Fiqh al-Bi'ah and Islamic criminal law. Using an empirical approach with qualitative methods, this research explores how the sasi mechanism contributes to community welfare and its relevance to Fiqh al-Bi'ah. The findings reveal that the implementation of the sasi tradition is managed by customary institutions with the authority to determine when sasi is enforced or lifted. There are two forms of traditional natural resource management in Negeri Iha: sasi laut (marine sasi) and sasi darat (land sasi). The study also shows that the sasi tradition's rules, goals, and punishments are similar to those in Fiqh al-Bi'ah. Both try to get the most suitable things done while doing the least environmental harm. Furthermore, violations of the sasi tradition are subject to customary sanctions, including physical punishment, fines, or spiritual consequences, such as the belief that violations could bring curses or illness as divine retribution. This research provides valuable insights into the harmony between the sasi tradition and the principles of Fiqh al-Bi'ah in preserving nature and maintaining the balance between humans and their environment.